Smart Mirror using Raspberry Pi - K.P. Vijayakumar, Yash Tandon, Vennam Prahasith (International Journal of Advanced Science and Technology, 2020)
A Smart mirror is an electronic device that can be a daily use device. The proposed system describes the design and implementation of a speech-controlled and interactive mirror known as “Smart Mirror”. The proposed system has two key features: facial recognition which increases the security of the mirror and also increases personalization within the mirror with the help of user profiling. Second, speech recognition which makes communicating with the mirror easier. The proposed system applies Local Binary patter histogram facial recognition. The system uses a microcontroller called ‘Raspberry Pi’ which integrates all the modules such as news, weather, date, time, sports updates etc. Experiment results shows that the proposed system outperforms all existing systems to achieve a success rate of 91.2%.